Mach-Zehnder interferometry with interacting trapped Bose-Einstein condensates - Grond, Julian; Hohenester, Ulrich; Schmiedmayer, Jörg; Smerzi, Augusto (Physical review. A, Atomic, molecular, and optical physics, 2011)
We theoretically analyze a Mach-Zehnder interferometer with trapped condensates and find that it is surprisingly stable against the nonlinearity induced by interparticle interactions. The phase sensitivity, which we study for number-squeezed input states, can overcome the shot noise limit and be increased up to the Heisenberg limit provided that a Bayesian or maximum-likelihood phase estimation strategy is used. We finally demonstrate the robustness of the Mach-Zehnder interferometer in the presence of interactions against condensate oscillations and a realistic atom-counting error.